The wolf of Wall Street - Scorsese, Martin; DiCaprio, Leonardo; Hill, Jonah, 1983-; Robbie, Margot; Belfort, Jordan (Hollywood, California : Paramount, 2014)
In the 1990s a wealthy stockbroker becomes involved in a securities scam that leads him to a life of crime and corruption.
Originally released as a motion picture in 2013.
Based on the memoir by Jordan Belfort.
DTS-HD Master Audio 5.1, wide screen 1.85:1.
Features: making of the film; UltraViolet enabled digital copy.
Camera, Rodrigo Prieto ; production design, Bob Shaw ; editor, Thelma Schoonmaker ; music supervisor, Randall Poster.
Leonardo DiCaprio, Jonah Hill, Margot Robbie, Matthew McConaughey, Kyle Chandler, Jon Bernthal, Jon Favreau, Rob Reiner.
Keywords: Belfort, Jordan -- Film adaptations; Stockbrokers -- Drama; Corruption -- Drama; Man-woman relationships -- Drama; Crime films; Dark comedy films; Fiction films; Video recordings for the hearing impaired; Based on the book; Feature films